Manajemen Strategi Badan Narkotika Nasional Dalam Upaya Pencegahan Penyalahgunaan Narkoba Di Kabupaten Donggala - Taufiq; Haris, Subhan; Labiro, Richard F. (JPS: Journal of Publicness Studies, 2025)
This study aims to examine the drug abuse prevention strategies implemented by the National Narcotics Agency of Donggala Regency (BNNK Donggala). The research method used is qualitative with a descriptive approach. To analyze BNNK Donggala’s strategies in preventing drug abuse, this study adopts Kooten’s theory, which consists of four strategic types: Organizational Strategy, Program Strategy, Resource Support Strategy, and Institutional Strategy. The types of data used include primary and secondary data, collected through observation, interviews, and documentation. The research findings show that the strategies implemented by BNNK Donggala are an extension of the national policies set by the central National Narcotics Agency (BNN), adapted to local conditions through mapping of drug-prone areas, community reports, surveys, and cross-sector coordination. The program targets are divided into two categories: individuals who have never used drugs and those who have tried or experimented with them. Prevention strategies for the first group are carried out through education and outreach, while the second group is approached through outpatient rehabilitation efforts. The main programs implemented include the Desa Bersinar (Drug-Free Village) Program, the Peer Teen Program (RTS), and the Anti-Drug Family Resilience Program. These programs emphasize community collaboration, the role of youth as agents of change, and the strengthening of family roles in early prevention. In addition, BNNK Donggala also conducts outreach through social media and direct field activities. For rehabilitation, outpatient services are provided through a clinic with procedures including interviews, screening, urine tests, and assessments. Clients with severe addiction are referred to the inpatient rehabilitation center in Makassar. Supporting strategies include human resource management, utilization of operational facilities, and institutional strengthening through cross-sectoral collaboration and the use of information technology, all of which contribute to the implementation of the program. In practice, BNNK Donggala adopts an integrated approach comprising preventive, repressive, and rehabilitative measures. Despite facing limitations in budget and personnel, synergy between the government, community, and stakeholders is a key factor in the success of the program.